PERCEIVED BENEFITS OF ICT-BASED RICE TECHNOLOGIES BY FARMERS AND AGRICULTURAL EXTENSION WORKERS - Gabrillo, Christina A; Torres, Cleofe S (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Information and Communication technologies (ICTs) enhance information flow and facilitate delivery of ICT-based agricultural extension for sustainable development. This study aimed to describe the benefits that farmers and agricultural extension workers (AEWs) derived from using these ICTs for rice technologies. These are the Pinoy Rice Knowledge Bank with Palay Check and Nutrient Manager for Rice Mobile that are accessible through the Internet and mobile phone, respectively. The study obtained the data through in- depth interviews with six rice farmers and five AEWs. Results showed that farmers’ access and use of rice ICTs: 1) make them look trendy, 2) facilitate finding of solutions to their farm problems, 3) enhance their farm skills on rice nutrient management, 4) link their produce to the local buyers, and 5) enable them to increase their crop yield. Likewise, the AEWs’ access to rice ICTs provide them with the following benefits: 1) rice ICTs have become part of their daily lives, 2) facilitate their extension work, 3) serve as a guide in giving advice to farmers, and 4) give them a sense of empowerment. The farmers followed some recommended techniques in the Palay Check. Both farmers and AEWs considered the high cost of mobile phone load and weak signal from cellular networks as problems in accessing rice ICTs. In general, however, the rice ICTs enhanced the AEWs’ work in promoting relevance, timeliness, and efficiency of their extension services. The study came up with a communication model for an improved extension delivery of ICT-based rice technologies.